Implementasi Model Pendidikan Inklusif dalam Pendidikan Jasmani untuk Anak Berkebutuhan Khusus - Arga Pradana; Selma Dewanti Laksmi; Putri Maharani (Atletik Karya: Jurnal Pendidikan dan Olahraga Aktual, 2024)
This study discusses the implementation of the inclusive education model in physical education for children with special needs (ABK) in elementary schools. The research method used is a case study with observations and interviews with teachers and students. The results of the study show that an inclusive approach in physical education helps improve social interaction, self-confidence, and motor skills of ABK. These findings emphasize the importance of adaptation strategies in physical learning for students with special needs.